2016
DOI: 10.1016/j.solmat.2016.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Controlled crystallization of CH3NH3PbI3 films for perovskite solar cells by various PbI2(X) complexes

Abstract: a b s t r a c tLead halide complexes are efficient precursors to obtain high quality perovskite films and high performance solar cells. However, how the lead halide complex affects the crystallization kinetics and thus the film quality of perovskite has not been systematically studied. Herein, two PbI 2 (X) complexes with different coordination strength of ligand X in complexation with PbI 2 (PbI 2 (DMF) and PbI 2 (DMSO)) are synthesized. The correlation between the morphology, evolution of the perovskite form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…As a result, crystallization becomes more controllable, which leads to uniform crystals, often with increased sizes. [23,24,33,34] Chemically, this complex can be described as the solvent molecules donating a free electron pair to the Pb 2+ ions. These so-called Lewis adducts are comparable to the lead-halide cage in the final perovskite structure.…”
Section: Crystallization Through Complex Formationmentioning
confidence: 99%
“…As a result, crystallization becomes more controllable, which leads to uniform crystals, often with increased sizes. [23,24,33,34] Chemically, this complex can be described as the solvent molecules donating a free electron pair to the Pb 2+ ions. These so-called Lewis adducts are comparable to the lead-halide cage in the final perovskite structure.…”
Section: Crystallization Through Complex Formationmentioning
confidence: 99%
“…Other work has also reported the deposition of PbI 2 ‐complex to promote an intermediate phase before the second conversion step with the idea of controlling perovskite crystallization. Among those applications, Fu et al compared the PbI 2 (DMF) and PbI 2 (dimethyl sulfoxide (DMSO)) complex precursors and found that perovskite film from PbI 2 (DMSO) shows reduced defects with higher quality . Cao et al claimed that when PbI 2 precipitates from DMF solution, the “Lewis acid–base adducts” of PbI 2 ‐ x DMF complex allows for the expansion of the lattice of PbI 2 , for MAI diffusion during the second immersion step .…”
Section: Introductionmentioning
confidence: 99%
“…c) Top‐surface SEM images of film prepared by pristine PbI 2 (left), PbI 2 (DMF) complex (middle), and PbI 2 (DMSO) complex (right). Reproduced with permission . Copyright 2016, Elsevier.…”
Section: Improved Film Formation By Pbi2 Complexmentioning
confidence: 99%
“…d) Absorbance with steady‐state PL (left) and carrier lifetime (right) for perovskite prepared by pristine PbI 2 (black), PbI 2 (DMF) (red), and PbI 2 (DMSO) (blue). Reproduced with permission . Copyright 2016, Elsevier.…”
Section: Improved Film Formation By Pbi2 Complexmentioning
confidence: 99%